203k views
0 votes
If f(x) = 3х2 +1 and g(x) = 1-х, what is the value of (f-g)(2)?

User Ephapox
by
5.6k points

1 Answer

3 votes

Answer:

(f - g)(2) = 13 - (-1) = 14

Explanation:

Please write f(x) = 3х2 +1 as f(x) = 3х^2 +1; use " ^ " to represent exponentiation.

We could either find the new function (f - g)(x) first and then substitute 2 for x, or we could evaluate both f and g at x = 2 and then subtract the results.

f(2) = 13 and g(2) = -1, so (f - g)(2) = 13 - (-1) = 14

User Naili
by
5.2k points